Época da poda mecanizada em laranjeiras doces 'Hamlin' e 'Pera' - Franco, Camila Kauffmann Becaro [UNESP] (2014)
The mechanized pruning of citrus plants brings benefits as auxiliary uniformity in the size and depth of the tree canopy, allowing standardization of cultivation, improving the efficiency of sprays and in many cases, reducing the cost of harvesting. However, there is need for specific recommendations for each group of varieties used in Brazilian citrus. With new planting techniques, especially new spacing, there was a reduction of the available plant development space and also the transit of machines, determining increased competition for water and light in the orchards in full production. Two trials were conducted with the aim to evaluate the best time to carry out pruning an orange tree on Hamlin and the other in 'Pera' sweet orange, implemented in 2005, both orchards located at Santa Luzia´s Farm, in Taquaral / SP - Brazil. The treatments represent different pruning times and were equal in both varieties (Hamlin and pear), harvests in 2011/12 and 2012/2013. In the conditions in which this research was conducted in the two consecutive years (2011/12 and 2012/13) it follows that for Hamlin pruning June to August were ideal. (after harvest and before flowering) and the Pera, the months of March to July were ideal for pruning. The pruning in two seasons did not affect productivity